Design and evaluation of Carvedilol nanocrystals sustained release tablets - Ashok Kumar Janakiraman, Balan Sumathi, T. Mohamed Saleem, S. Ramkanth, P. Odaya Kumar, Gopal Venkatachalam (Journal of Applied Pharmaceutical Science, 2017)
The present study was undertaken to develop and evaluate the carvedilol nanocrystals sustained release (SR) tablets. The tablets were prepared by direct compression method using hydroxy propyl methyl cellulose (HPMC) and ethyl cellulose (EC) polymers. The prepared tablets were evaluated in terms of their pre-compression studies, post-compression parameters, in vitro dissolution and drug release kinetic. The tableting of blend showed good pre-compression properties and the formulated tablets were exhibited desired post-compression characters. The in vitro drug release were performed in the United States pharmacopoeia (USP) apparatus-II (Paddle) using phosphate buffer (pH 6.8). The formulation CT5 was selected as the optimized formulation by an in vitro drug release for 24 hrs with the release of 99.46%. Drug release kinetics showed the best fit to Higuchi’s equation, and they exhibit diffusion dominated mechanism. The comparative in vitro release study showed that the formulation CT5 has better control over the release of drug (99.46%) when compare to reference product (73.64%) for 24 hrs. Thus overall result indicate that the carvedilol nanocrystal using SR tablets is more discriminative approach for better release and prolong action.
Keywords: Carvedilol nanocrystals, Sustained release, In vitro dissolution and Drug release kinetic.